Implementasi dan Evaluasi Sistem Failover Otomatis Berbasis Netwatch pada Router Mikrotik Dual-ISP untuk Meningkatkan Ketersediaan Jaringan Apotek Farmaku - Boy Yuliadi; Rasto (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study contributes by proposing and implementing an automated failover–failback mechanism based on Mikrotik Netwatch for multi-homed Internet connectivity, which has not been widely explored in the context of pharmacy information systems, and by validating its effectiveness through empirical testing in a production-like environment. Unlike prior work that is largely conceptual or simulation-oriented, this research evaluates the system in an end-to-end manner at both the control plane (router-level monitoring and switching) and the data plane (client-side traffic continuity). The system is developed following the Network Development Life Cycle (NDLC) methodology, encompassing analysis, design, simulation, simulation testing, and deployment. A dual-ISP architecture is implemented, in which Netwatch continuously probes upstream reachability and triggers automated route switching upon link degradation or failure, as well as automatic restoration upon link recovery. Experimental results indicate that the system achieves an average failover time of approximately 5 seconds, with minimal packet loss and no perceptible service interruption for end users. The failback mechanism also operates autonomously and stably. Overall, router- and client-side performance measurements confirm that the proposed solution effectively enhances network resilience and service availability in environments with high availability requirements.